Expanding literacy practices across multiple modes and languages for multilingual students - De Oliveira, Luciana C.; Smith, Blaine E. (University of Miami School of Education and Human Development series, 2019)
Literacy practices have changed over the past several years to incorporate modes of representation much broader than language alone, in which the textual is also related to the visual, the audio, the spatial, etc. This book focuses on research and instructional practices necessary for integrating an expanded view of literacy in the classroom that offers multiple points of entry for all students. Projects highlighted in this book incorporate multiple modes of communication (e.g., visual, aural, textual) through various digital and print-based written formats. In addition, this book particularly focuses on the possibilities that this expanded view of literacy holds for emergent to advanced bilingual students and specific scaffolds necessary for supporting them. Our focus is specifically multilingual students as classrooms across the United States and other English-speaking countries around the world become more and more diverse. The book considers educators as active participants in social change and contributors to our overall goal of social justice for all. This book grew out of work conducted by doctoral students and former doctoral students, now faculty at various universities, from the Language and Literacy Learning in Multilingual Settings (LLLMS) specialization in the Department of Teaching and Learning at the School of Education and Human Development at the University of Miami, Florida. The most outstanding feature of this work is the breadth of examples for integrating literacy in the classroom, as well as the specific instructional strategies provided for supporting multilingual students. This volume is unique in tackling both literacy and specific scaffolding for multilingual students. Additionally, the chapters here collectively aim to go beyond describing research to also provide a variety of classroom connections for practitioners and implications for teacher education.